2011
DOI: 10.1074/jbc.m111.235903
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PRIP, Phospholipase C-related, but Catalytically Inactive Protein, in Bone Formation

Abstract: PRIP (phospholipase C-related, but catalytically inactive protein) is a novel protein isolated in this laboratory. PRIP-deficient mice showed increased serum gonadotropins, but decreased gonadal steroid hormones. This imbalance was similar to that for the cause of bone disease, such as osteoporosis. In the present study, therefore, we analyzed mutant mice with special reference to the bone property. We first performed three-dimensional analysis of the femur of female mice. The bone mineral density and trabecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
1
12
2
Order By: Relevance
“…We reported that the increased bone mass observed in PRIP-KO mice was caused by enhanced bone formation, and BMP stimulation of newborn calvaria cells caused the prolonged phosphorylation of Smad1/5, probably explaining the enhanced bone formation as one of the many underlying mechanisms [Tsutsumi et al, 2011]. The present study was undertaken to investigate the mechanisms of how PRIP is implicated in the BMP signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We reported that the increased bone mass observed in PRIP-KO mice was caused by enhanced bone formation, and BMP stimulation of newborn calvaria cells caused the prolonged phosphorylation of Smad1/5, probably explaining the enhanced bone formation as one of the many underlying mechanisms [Tsutsumi et al, 2011]. The present study was undertaken to investigate the mechanisms of how PRIP is implicated in the BMP signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Smad1/5 is a main factor for BMP signaling and the phosphorylation of Smad1/5 C-terminal is an initial step to transmit the BMP signaling cascade following BMP binding to the receptors [Massague et al, 2005;Katagiri, 2008]. We previously reported that Smad1/5 phosphorylation by BMP stimulation in KO calvaria cells was more evident than that in WT cells; particularly after the peak than at a peak, the results led us to assume that PRIP might be involved in the dephosphorylation process [Tsutsumi et al, 2011].…”
Section: Phosphorylation Of Smad1/5 In Response To Bmp Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…PRIP has a number of binding partners, including the catalytic subunit of protein phosphatase 1α (PP1α) and PP2A [512,513] and the phosphorylated (active) form of Akt [514] in addition to IP 3 and PIP 2 [515]. PRIP gene-deficient mice ( prip −/− ), genetically deficient in type 1 or type 2 isoforms or both, brought light the physiological functions of PRIP: modulation of GABAA receptor signaling [516], dysfunction of reproduction, negative regulation of multiple-hormone secretion [517] and bone properties [518]. PRIP is involved in the phosphorylation-dependent modulation of exocytosis in PC-12 cells [519].…”
Section: Plc-related But Catalytically Inactive Proteinmentioning
confidence: 99%
“…Exocytosis of various peptide hormones, such as gonadotropins and insulin, was up-regulated in prip −/− mice, indicating that PRIP is likely to be involved in dense core vesicle exocytosis in a negative manner. PRIP is implicated in the regulation of bone formation in a negative manner, partly through the regulation of SMAD phosphorylation [518]. Since PC-PLC contributes to the progression of atherosclerosis, it was proposed that pharmacological blockade of PC-PLC is a possible approach to atherosclerosis therapy.…”
Section: Plc-related But Catalytically Inactive Proteinmentioning
confidence: 99%